Non‐classical Design of High‐Efficiency Sensitizers for Dye‐Sensitized Solar Cells. Issue 5 (12th January 2018) - Nguyen, The‐Duy; Wu, Chun‐Guey
Abstract : The dye regeneration step in a dye‐sensitized solar cell (DSSC) affects significantly the device efficiency. To be able to predict the dye regeneration efficiency by the electrolyte this paper provides a facile way to design high‐efficiency sensitizers for DSSC. This paper proposes, for the first time, a simple and ingenious way to identify the dye regeneration sites and their relative efficiencies when a specific electrolyte is used. Two steps are proposed to identify the dye regeneration sites and their relative regeneration efficiencies: (1) drawing all the resonance structures of the oxidized dye to determine the regeneration sites, and (2) choosing the most favored site for dye regeneration as the chemically softest (when the redox couple used is soft I − /I3 − pair) and the least spatially hindered site. The regeneration sites identified by the resonance structures are consistent with the β‐LUSO (β lowest unoccupied spin orbital) distribution, which is generally used for identifying the dye regeneration sites, calculated with DT‐DFT theory. The relative dye regeneration efficiency and photovoltaic performance of both ruthenium and metal‐free organic dyes predicted by the method reported here are supported by experimental data and the proposed dye regeneration mechanism. Several types of dye molecules are used to demonstrate the correctness of this new tool. This non‐classical tool, which uses the well‐known chemical knowledge of the resonance structure and hard–soft acid–base principle, without any computer calculation or physicochemical measurement, provides a very simple and powerful tool to quickly conceive high‐efficiency sensitizers for DSSCs. Abstract : The regeneration sites identified by the resonance structures of an oxidized dye cation are conformity with the β‐LUSO distribution calculated from the DFT theory, which can be used to evaluate the photovoltaic performance of the dye when applying in DSSC.